PENDUGAAN DEFISIT DAN SURPLUS AIR UNTUK PENGEMBANGAN TANAMAN JAGUNG (ZEA MAYS L.) DI KABUPATEN GORONTALO DENGAN MENGGUNAKAN MODEL SIMULASI NERACA AIR - Yunnita Rahim; Johannes E. X. Rogi; Samuel D. Runtunuwu (AGRI-SOSIOEKONOMI, 2015)
This study aims to apply the water balance simulation model developed by Handoko (1992) for estimating the deficit and surp4lus water for the development of corn plants in the province of Gorontalo. This study was implemented from April to August 2014 in the District of Gorontalo. The study metods included field studies and modeling of water balance using a simulation model by Handoko (1992). The results showed that the period of water deficit was found in August and September where rainfall (Ch) is smaller than potential evapotranspiration (ETP) whereas periods of surplus water in the district of Gorontalo found in January to July and October to December where rainfall (Ch) exceeds potential evepotranspiration (ETP).